Measuring the efficiency of reduction gearboxes for electric utility vehicles during specific driving cycles - Petr, Tomas (Strojniški vestnik, 2022)
This paper presents the results and the procedure for measuring the efficiency of a single-speed reduction gearbox developed for an autonomous electric utility vehicle. The resulting efficiency of the gearbox was investigated on three different driving cycles, which were selected because their speed profiles most closely matched the expected use of the autonomous vehicle. The required torque for each cycle was obtained from simulations of the vehicle’s driving behaviour including its predicted mass and dimensional parameters after a given driving cycle. The results of this research represent the achieved efficiency and average power loss of the gearbox on each driving cycle. The resulting gearbox efficiency was around 50 % in the predominant areas of driving cycles.
Keywords: driving cycle; efficiency; electric vehicles; električna vozila; električni pogon; gearboxes; izkoristek; menjalniki; powertrain; prenos moči; transmisija; vozni cikel